Radiographer reporting: A literature review to support cancer workforce planning in England. Issue 2 (May 2019) - Culpan, G.; Culpan, A.-M.; Docherty, P.; Denton, E.
Abstract: Objective: Clinical Imaging contributes to screening, diagnosis, planning and monitoring of treatment and surveillance in cancer care. This literature review summarises evidence about radiographer reporting to help imaging service providers respond to Health Education England's 2017 Cancer Workforce Plan project to expand radiographer reporting in clinical service provision. Key findings: Papers published between 1992 and 2018 were reviewed (n = 148). Evidence related to dynamic examinations (fluoroscopy, ultrasound) and mammography was excluded. Content was analysed and summarised using the following headings: clinical scope of practice, responsibilities, training, assessment, impact in practice and barriers to expansion. Radiographer reporting is well established in the United Kingdom. Scope of practice varies individually and geographically. Deployment of appropriately trained reporting radiographers is helping the NHS maintain high quality clinical imaging service provision and deliver a cost-effective increase in diagnostic capacity. Conclusion: Working within multiprofessional clinical imaging teams, within a defined scope of practice and with access to medical input when required, reporting radiographers augment capacity in diagnostic pathways and release radiologist time for other complex clinical imaging responsibilities. Highlights: Radiographers in England report a wide range of examinations and referrals. Definitive reporting requires a formal Masters level education qualification. Radiographer reporting is associated with a range of service delivery improvements. Professionals can experience improved job satisfaction and enhanced team working. Reporting radiographers augment imaging capacity in cancer care pathways.